ANALISIS EVALUASI KINERJA PEGAWAI DALAM MENINGKATKAN PELAYANAN PUBLIK PADA PT. PERMODALAN NASIONAL MADANI MEKAR KABUPATEN NIAS - Bu'ulolo, Fazarman; Waruwu, Suka'aro; Hulu, Fatolosa; Mendrofa, Yupiter (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
To anticipate competition in this service sector, it has certainly become a necessity for service providers to maintain quality, by demonstrating their ability to provide the most effective and efficient services at a low cost and with qualified Human Resources. This study focuses on the obstacles and barriers to health services and the main duties and functions of nurses at the UPTD Awaai Health Center. And this study aims to explore what obstacles are faced by nurses in improving health services, and to find out what strategies are carried out to improve the performance of nurses at the UPTD Awaai Health Center. The research conducted by the author here is using a field research method with a qualitative approach. This research was conducted at the UPTD Awaai Health Center, Sitolu Ori District, North Nias Regency. In collecting data, the author used interview techniques while in the discussion, a descriptive method was used, namely a method that describes the conditions that occur in the field. From the results of the research conducted by the author at the UPTD Awaai Health Center, Sitolu Ori District, North Nias Regency, namely the implementation of health services, there are several obstacles experienced by nurses in providing services to patients who are being treated. These obstacles are that the Health Center experiences a lack of adequate medical equipment or facilities. To improve the quality of health services, several strategies can be carried out by the Health Center, including: To improve the performance of health nurses, regular training and professional development programs are very important. Second, strengthening service management, such as a technology-based queuing system to reduce waiting times, will increase efficiency.